Daunorubicin and Its Active Metabolite Pharmacokinetic Profiles in Acute Myeloid Leukaemia Patients: A Pharmacokinetic Ancillary Study of the BIG-1 Trial - Guillaume Drevin; Marie Briet; Caroline Bazzoli; Emmanuel Gyan; Aline Schmidt; Hervé Dombret; Corentin Orvain; Aurelien Giltat; Christian Recher; Norbert Ifrah; Philippe Guardiola; Mathilde Hunault-Berger; et al. (MDPI AG, 2022)
Daunorubicin pharmacokinetics (PK) are characterised by an important inter-individual variability, which raises questions about the optimal dose regimen in patients with acute myeloid leukaemia. The aim of the study is to assess the joint daunorubicin/daunorubicinol PK profile and to define an optimal population PK study design. Fourteen patients were enrolled in the PK ancillary study of the BIG-1 trial and 6-8 samples were taken up to 24 h after administration of the first dose of daunorubicin (90 mg/m2/day). Daunorubicin and daunorubicinol quantifications were assessed using a validated liquid chromatography technique coupled with a fluorescence detector method. Data were analysed using a non-compartmental approach and non-linear mixed effects modelling. Optimal sampling strategy was proposed using the R function PFIM. The median daunorubicin and daunorubicinol AUC0-tlast were 577 ng/mL·hr (Range: 375-1167) and 2200 ng/mL·hr (range: 933-4683), respectively. The median metabolic ratio was 0.32 (range: 0.1-0.44). Daunorubicin PK was best described by a three-compartment parent, two-compartment metabolite model, with a double first-order transformation of daunorubicin to metabolite. Body surface area and plasma creatinine had a significant impact on the daunorubicin and daunorubicinol PK. A practical optimal population design has been derived from this model with five sampling times per subject (0.5, 0.75, 2, 9, 24 h) and this can be used for a future population PK study.